Handbook of international futurism - Berghaus, Günter (De Gruyter reference., 2019)
The Handbook of International Futurism is the first reference work ever to presents in a comparative fashion all media and countries in which the movement, initiated by F.T. Marinetti in 1909, exercised a particularly noteworthy influence. The handbook offers a synthesis of the state of scholarship regarding the international radiation of Futurism and its influence in some fifteen artistic disciplines and thirty-eight countries. While acknowledging the great achievements of the movement in the visual and literary arts of Italy and Russia, it treats Futurism as an international, multidisciplinary phenomenon that left a lasting mark on the manifold artistic manifestations of the early twentieth-century avant-garde. Hundreds of artists, who in some phase in their career absorbed Futurist ideas and stylistic devices, are presented in the context of their national traditions, their international connections and the media in which they were predominantly active. The handbook acts as a kind of multi-disciplinary, geographical encyclopaedia of Futurism and gives scholars with varying levels of experience a detailed overview of all countries and disciplines in which the movement had a major impact.